2023
DOI: 10.5603/fm.a2022.0074
|View full text |Cite
|
Sign up to set email alerts
|

Effects of liquid diet intake on nerve growth in salivary glands of growing rats

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited. Articles in "Folia Morphologica" are listed in PubMed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…If the body weights of animals had differed between the pellet diet group and the liquid diet group, it would have become impossible to judge whether tissue alterations were caused directly by intake of liquid diet or by deterioration of general conditions. In previous studies, liquid diet was prepared by mixing one part of a powdered form of the pellet diet with two parts of water, and no differences in rat body weight were identified between liquid-and pellet-fed groups (12,(28)(29)(30)(31)(32)(33). Therefore, this liquid diet was prepared and used in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the body weights of animals had differed between the pellet diet group and the liquid diet group, it would have become impossible to judge whether tissue alterations were caused directly by intake of liquid diet or by deterioration of general conditions. In previous studies, liquid diet was prepared by mixing one part of a powdered form of the pellet diet with two parts of water, and no differences in rat body weight were identified between liquid-and pellet-fed groups (12,(28)(29)(30)(31)(32)(33). Therefore, this liquid diet was prepared and used in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The parotid gland weight remains low due to the inhibition of increases in acinar cell size and low proliferative activity of acinar cells (30). Furthermore, a recent study showed that a liquid diet inhibited the growth of parasympathetic nerves in the parotid gland (28). On the contrary, gland weight, acinar cell size, acinar cell proliferation (33), and parasympathetic nerve growth (28) were not affected in the submandibular glands of growing rats kept on a liquid diet.…”
Section: Introductionmentioning
confidence: 99%